PERANCANGAN E-MAGAZINE ’NYAWANG GALUH’ SEBAGAI INOVASI PELAYANAN PUBLIK DALAM MEMBERIKAN INFORMASI PARIWISATA KABUPATEN CIAMIS BERBASIS BAHASA SUNDA - Shafira Eka Putri; Abung Supama Wijawa (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This research aims to design the Nyawang Galuh e-magazine as a public service innovation providing Sundanese-language tourism information for Ciamis Regency. The background of this research is based on the suboptimal availability of tourism promotional media capable of reaching a wide audience and the need to preserve regional languages ​​in the digital age. The research method used was a qualitative approach with design-based research through data collection techniques such as observation, interviews, documentation, and literature review. The results show that the Nyawang Galuh e-magazine is a communicative, visually appealing, and easily accessible information medium for the public, especially the younger generation. The application of the Integrated Marketing Communication (IMC) concept in the design of this media resulted in consistent and effective message delivery in promoting the tourism potential of Ciamis Regency. Furthermore, the use of Sundanese in this e-magazine contributes to efforts to preserve local culture. Thus, the Nyawang Galuh e-magazine can be categorized as a digital-based public service innovation that functions not only as a promotional medium but also as a means of education and preservation of regional languages ​​in the modern era.